The exploration of miRNAs and mRNA profiles revealed the molecular mechanisms of cattle-yak male infertility - Zhao, Shaokang; Sun, Wenqiang; Chen, Shi-Yi; Li, Yuchao; Wang, Jie; Lai, Songjia; Jia, Xianbo (Frontiers in Veterinary Science, 2022)
Cattle-yak, the first-generation offspring of cattle and yak, inherited many excellent characteristics from their parents. However, F1 male hybrid infertility restricts the utilization of heterosis greatly. In this study, we first compared the testicular tissue histological characteristics of three cattle, three yaks, and three cattle-yak. Then we explored the miRNA profiles and the target functions of nine samples with RNA-seq technology. We further analyzed the function of DE gene sets of mRNA profiles identified previously with GSEA. Testicular histology indicated that the seminiferous tubules became vacuolated and few active germ cells can be seen. RNA-seq results showed 47 up-regulated and 34 down-regulated, 16 up-regulated and 21 down-regulated miRNAs in cattle and yaks compared with cattle-yak, respectively. From the intersection of DE miRNAs, we identified that bta-miR-7 in cattle-yak is down-regulated. Target prediction indicated that the filtered genes especially MYRFL, FANCA, INSL3, USP9X, and SHF of bta-miR-7 may play crucial roles in the reproductive process. With further network analysis and GSEA, we screened such hub genes and function terms, we also found some DE gene sets that enriched in ATP binding, DNA binding, and reproduction processes. We concluded that bta-miR-7 may play an important role in influencing fecundity. Our study provides new insights for explaining the molecular mechanism of cattle-yak infertility.